FORMATION OF VISUAL AND VISUAL THINKING OF CHILDREN THROUGH GAME ACTIVITIES - Oripova Nodima Halilovna; Keldiarova Vazira Botyrovna (Western European Studies, 2024)
This article reveals the content and essence of the formation of thinking in preschool children, in particular, the features of the development of visual-figurative thinking in children. Considering that the development of thinking in children is inextricably linked with play activity, we are talking about the possibilities of being invisible and being formed in this process of forming visual-figurative thinking. Also in this regard, the competency-based and methodological knowledge required from teachers, requirements and several creative Everest methods are listed
Keywords: preschool age; thinking; game activity